2012
DOI: 10.1289/ehp.1103928
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Silver Nanoparticles Inhibits Selenoprotein Synthesis and the Activity of Thioredoxin Reductase

Abstract: Background: Silver nanoparticles (AgNPs) and silver (Ag)-based materials are increasingly being incorporated into consumer products, and although humans have been exposed to colloidal Ag in many forms for decades, this rise in the use of Ag materials has spurred interest into their toxicology. Recent reports have shown that exposure to AgNPs or Ag ions leads to oxidative stress, endoplasmic reticulum stress, and reduced cell proliferation. Previous studies have shown that Ag accumulates in tissues as silver su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 49 publications
4
49
0
Order By: Relevance
“…Increased ROS production after exposure to nanoparticles has been linked in several studies. [50][51][52] It has also been reported that oxidative stress seen in different types of cells like fibroblast, muscle, and colon was due to apoptosis induced by exposure to AgNPs. 50 The formation of free radicals and other toxic oxidizing agents can be prevented using some enzymatic antioxidants such as GSH reductase, CAT, Px, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ROS production after exposure to nanoparticles has been linked in several studies. [50][51][52] It has also been reported that oxidative stress seen in different types of cells like fibroblast, muscle, and colon was due to apoptosis induced by exposure to AgNPs. 50 The formation of free radicals and other toxic oxidizing agents can be prevented using some enzymatic antioxidants such as GSH reductase, CAT, Px, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased levels of GSH after exposure to AgNPs may be due to complexing of AgNPs with thiol groups or to increasing use of GSH to downplay the effect of free radicals after exposure to the nanoparticles. 52,53 These nanoparticles have a strong affinity for thiol groups and may therefore predispose to a decrease in GSH content, thereby leading to the formation of complexes between radical species and cellular proteins or other biomolecules. Se is an essential element with beneficial antioxidant property and is a structural component of several enzymes like GSH-Px and Trx reductase, and has been found to have detoxification effects on various heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the gold nanoclusters inhibit the activity of TrxR, leading to higher levels of reactive oxygen species and apoptosis in HeLa cells. Silver nanoparticles have also been reported to inhibit selenoprotein synthesis, and the activity of TrxR in in vitro studies, resulting in an increase in oxidative stress [65].…”
Section: Thioredoxin Reductase Binding Studiesmentioning
confidence: 99%
“…GSH is an antioxidant that can quench free radicals or serve as a substrate for other antioxidant enzymes, such as Glutathione Peroxidase and Glutathione Reductase (↓GSH). The decreased levels of ↓GSH after exposure to silver nano particles may be due to complexing of silver nano particles with Thiol groups leads to production of ROS and oxidative stress [22,23] or increase use of ↓GSH downplay the effect of free radicals after exposure to silver nano particles [24]. These nano particles have a strong affinity for thiol groups [22] and may therefore predispose to a decrease in ↓GSH content, there by leading to the formation of complexes between radical species and cellular proteins or other biomolecular structure.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased levels of ↓GSH after exposure to silver nano particles may be due to complexing of silver nano particles with Thiol groups leads to production of ROS and oxidative stress [22,23] or increase use of ↓GSH downplay the effect of free radicals after exposure to silver nano particles [24]. These nano particles have a strong affinity for thiol groups [22] and may therefore predispose to a decrease in ↓GSH content, there by leading to the formation of complexes between radical species and cellular proteins or other biomolecular structure. Our results show that 6-19-day oral repeated dosing of AgNPs during pregnancy caused oxidative stress in maternal hepatic tissues, as evidenced by a decrease in liver CAT and ↓GSH activities at a dose of 0.5 and 1 mg/kg/day, but did not cause any significant developmental toxicity in same dose in Swiss Albino mice.…”
Section: Discussionmentioning
confidence: 99%